Comparing suitability of sub 1 GHz and WiFi transceivers for RSS-based indoor localisation - Fudickar, Sebastian; Valentin, M (IPIN 2014 - 2014 International Conference on Indoor Positioning and Indoor Navigation, 2014)
WiFi transceivers are available in most hand-held devices and thus are well suited for indoor localisation. However, their critical high-power consumption is challenging acceptable battery runtimes for frequent localisation (such as tracking). Alternative transceivers that operate at frequencies of 868 MHz can be expected to be included in upcoming smartphones and achieve similar transmission ranges but have significant lower power-consumption. Thus, this article analyses if these alternative transceivers-so-called Sub GHz transceivers-are better suited for frequent indoor localisation, than WiFi transceivers. Therefore, localisation accuracies and battery runtimes have been analysed via trace-driven empirical studies and battery runtime tests. The results indicate that Sub GHz transceivers are better suited than WiFi transceivers in both considered terms and are especially more robust regarding the influence of obstacles and peoples. Sub GHz transceivers achieve significant lower RSS errors and are less influenced by wall attenuations. Consequently, their localisation achieved ca. 1 m more accurate median error distances than the corresponding versions that utilise WiFi transceivers. In addition, the battery runtimes are extended by 48% when using Sub GHz transceivers instead of WiFi transceivers.